Satisfaction among caregivers of beneficiaries with the services provided at the well-baby clinic of a tertiary care hospital, Kolkata - Pattanayak, Shalini; Naskar, Somnath; Partha Pratim Pal,; Mausumi Basu,; Ankita Mishra,; Chakrabarti, Sreetama (Asian Journal of Medical Sciences, 2023)
Background: Well-baby clinics (WBC) are health facilities for providing primary care, including immunization services to infants and children. Caregivers’ satisfaction is a vital indicator of the quality of healthcare services provided. Aims and Objectives: This study aims to assess the caregivers’ satisfaction with the services provided at the WBC of a tertiary care hospital in Kolkata, West Bengal and to identify the associated sociodemographic factors. Materials and Methods: A descriptive-type of observational study with a cross-sectional design, was conducted from June to July 2022, using a predesigned pretested and structured schedule, among 106 caregivers of beneficiaries attending WBC. Satisfaction was assessed using 24 items answered on a 5-point Likert scale, ranging from “highly satisfied” to “highly dissatisfied.” Data were tabulated in MS Excel 2021 and analyzed using statistical package for the social sciences v25.0. Bivariate Logistic Regression was performed to examine the association of sociodemographic factors with caregivers’ satisfaction. Results: High satisfaction with the services was observed among 52.8% participants. Least number of caregivers were satisfied with the vaccination services. Caregivers’ gender, mothers’ education and beneficiaries’ gender were found to be statistically significant with their satisfaction. Furthermore, the female caregivers had lower odds of statistically significant high satisfaction than the males. Conclusion: Almost half of the caregivers were less satisfied with the services offered at the WBC, while the least number of caregivers were satisfied with the vaccination services. Extensive research is needed to identify the factors contributing to the satisfaction of caregivers with the services, mainly vaccination.